Effect of operating conditions on characterization and stabilization of cyclodextrin glycosyltransferase (CGTASE) - Nur 'Izzaty Hazera, Nazar (2016)
Cyclodextrin glycosyltransferase (CGTase) is an enzyme that produces cyclodextrin (CD) from starch under catalytic reaction. It is an important industrial enzyme which mostly used in food and pharmaceutical industry. The purpose of this study is to determine the effect of operating conditions on characterization and stabilization of CGTase to improve the production of cyclodextrin (CD) in the future. Therefore, the effect of starch concentration and pH on the characterization of CGTase were studied. The effect of pH and temperature on stabilization of CGTase were investigated. The best starch concentration and pH on characterization of CGTase were 3% w.v and pH 6 respectively. The most stable conditions of CGTase were detected at pH 6-8 and temperature of 40-60˚C. By using these optimum conditions, the CD production may improve in the future which in turn may be beneficial to industrial uses.